ANDROGENESIS ABILITY IN COMMON WHEAT EUPLASMIC LINES AND ALLOPLASMIC RECOMBINANT LINES (H. VULGARE)-T. AESTIVUM POSSESSING 1RS.1BL AND 7DL-7AI TRANSLOCATIONS AND PRODUCTION OF DOUBLE HAPLOID LINES - T. S. Osadchaya; L. A. Pershina; N. V. Trubacheeva; I. A. Belan; L. P. Rosseeva; E. P. Devyatkina (Вавиловский журнал генетики и селекции)
Androgenesis ability was studied in anther cultures of euplasmic lines of common wheat and alloplasmic recombinant lines (H. vulgare)-T. aestivum with 1RS.1BL and 7DL-7Ai translocations. The ability to produce androgenic structures and plantlet regeneration are suppressed in lines carrying both translocations. Alloplasmic recombinant lines (H. vulgare)-T. aestivum with 1RS.1BL and 7DL-7Ai translocations, as well as alloplasmic lines with 1RS.1BL translocation, are characterized by increased ability to create androgenic structures, including polyembryos, and plantlet regeneration as compared to euplasmic lines. The inducing reciprocal influence of barley cytoplasm and rye chromosome 1RS on the androgenesis ability of lines (H. vulgare)-T. aestivum with 1RS.1BL and 7DL-7Ai translocations is discussed. Double haploid lines were developed from androgenic plants with spontaneously doubled chromosome numbers and restored fertility. Of the lines carrying the translocations, the most promising with regard to the manifestation of commercially valuable traits and resistance to diseases were selected in order to utilize them in breeding programs.